STUDENT PERCEPTION OF THE ADVANTAGES AND CHALLENGES OF USING CHATGPT (ARTIFICIAL INTELLIGENCE) FOR ACADEMIC ASSIGNMENTS - Rajali Saragih; Juliandri; Nuranisah (Yayasan Sinergi Multidimensi Kreatif, 2025)
The presence of Artificial Intelligence (AI) has an influence on various areas of life. One of the products of AI is ChatGPT which is a product of a non-profit company, namely OpenAI which was established in 2015. The presence of ChatGPT has received various responses from the public, especially in the academic field who debate the use of ChatGPT. The use of ChatGPT is feared to threaten academic integrity, while on the other hand, there are those who argue that ChatGPT can facilitate work in the academic world. This research aims to explore students' perceptions of the advantages and challenges of using Artificial Intelligence (AI), especially ChatGPT, in completing academic assignments. As one of the AI technologies based on natural language processing, ChatGPT has been widely used to support various academic needs, such as information searching, essay preparation, and idea development. The main advantages identified include time efficiency, ease of access to information, and increased productivity. However, the challenges faced include the risk of plagiarism, lack of mastery of the material, and potential dependence on technology. This study uses a survey method to collect data from students of the computer systems study program of the University of Panca Budi Development. The results showed that students had diverse views, with most appreciating the benefits, but still worried about the impact on academic ethics and the development of critical thinking skills. This finding is expected to be a reference for educational institutions in formulating policies for the ethical and effective use of AI technology in the learning process.